EFFECTIVENESS OF CLINICALLY SUPERVISED EXERCISE PROGRAM ASCOMPARED TO HOME BASED EXERCISE PROGRAM ON PAIN ANDDISABILITY IN KNEE OSTEOARTHRITIS - Wahaj Sheikh (Baqai Journal of Health Sciences)
ABSTRACT The Objectives of this study was to compare the effectiveness of clinically supervised exercise program with home based exercise program on pain and disability in knee osteoarthritis. Individuals with pain full knee were enrolled from the OPD of IPM & R, Dow University of Health Sciences (DUHS), Karachi. Then patients were indiscriminately assigned to both groups with age and gender alike. Numeric pain rating scale was used for assessment of pain and Lequesne Index for functional capacity, at initial and final session of intervention. Study method was conversed with patients and transcribed permission of the subjects was signed. Design of Study is quasi experimental design and the Study setting: Study has conducted at Institute of Physical therapy Medicine & Rehabilitation, Dow University of Health Sciences, Karachi. Sample size: I have taken 30 subjects per groups. Interventions: Both groups performed same amount of exercise (25 minutes for four consecutive days about 4 weeks. Experimental group performed these exercise in clinical areas in front of physiotherapist while control group perform these exercises at home. However control group has visited once in a week only. Result for evaluation of data SPSS 20 version was used. Mean standard deviation age weight quantitative variables were calculated. Clinically supervised exercise group shows better results compared with control group with P- value of 0.001.